Chapter La terminologia per il CLIL in lingua straniera e in italiano L2 - GILARDONI, Silvia (Proceedings e report, 2021)
In this paper we examine the treatment of terminology in CLIL context (Content and language integrated learning), through the analysis of a corpus of subject textbooks in a foreign language and in Italian as a second language. After introducing the CLIL methodology and its application in the field of foreign language and Italian as a second language teaching as regards the Italian context, we consider the role of terminology in CLIL environment. Then we present the results of the analysis of the corpus, which consists of CLIL textbooks in English for the secondary school and of subject textbooks in Italian as a second language for non-native speakers of secondary school and adult migrants who need the qualification of Italian secondary school. The analysis of the treatment of terminology in the corpus allows to outline methodological suggestions to integrate the terminological approach into teaching practice in different CLIL contexts.